The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/01.tp.0000255567.80203.bd
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Transplantation Using Extended-Donor Criteria Organs for Systemic Amyloidosis Complicated by Heart Failure

Abstract: Cardiac transplantation for amyloid patients with extended-donor criteria organs followed by either stem cell or liver transplantation is associated with improved survival compared to patients not transplanted. Short- to intermediate-term survival is similar to patients receiving heart transplantation for other indications. This clinical management strategy provides cardiac amyloid patients a novel therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 38 publications
1
40
0
6
Order By: Relevance
“…71 Twenty-five patients with systemic amyloidosis and HF were included in the study. Twelve patients with amyloidosis were transplanted.…”
Section: Amyloidmentioning
confidence: 99%
“…71 Twenty-five patients with systemic amyloidosis and HF were included in the study. Twelve patients with amyloidosis were transplanted.…”
Section: Amyloidmentioning
confidence: 99%
“…This study also showed that relapse of the plasma cell dyscrasia after ASCT was associated with characteristic echocardiographic evidence of cardiac amyloidosis and rise in serum NT-pro-BNP. Maurer et al, reported on 10 patients who underwent HTx for AL amyloidosis (Maurer et al, 2007). In this study among eight patients who received subsequent ASCT, two died from sepsis and lymphoma.…”
Section: P=004mentioning
confidence: 89%
“…In 2004, Skinner et al reported a complete hematologic response, defined as no evidence of an underlying plasma cell dyscrasia one year after treatment, in 40% of patients with primary AL amyloidosis who received high-dose melphalan followed by autologous stem cell transplantation (Dey et al, 2010;Skinner et al, 2004). Recently cardiac transplantation followed by high-dose chemotherapy and ASCT has been shown to be feasible in carefully selected patients with AL amyloidosis and severe HF (Dey et al, 2010;Gillmore et al, 2006;Kristen et al, 2009;Lacy et al, 2008;Maurer et al, 2007;Mignot et al, 2008;Sattianayagam et Time (months)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore timing of heart transplant is especially crucial in this patient setting since patients might miss the window of opportunity for hematologic treatment. Extended donor criteria have been advocated and may be utilized to facilitate a timely transplant in selected cases [123]. Another approach would be to consider heart transplant after successful hematological treatment including ASCT [124], but this strategy is fraught with more hazard, because of the high risk of death among ASCT AL patients with cardiac amyloid bad enough to require cardiac transplantation..…”
Section: High Dose Chemotherapy With Autologous Hematopoietic Stem Cementioning
confidence: 99%